Audiovisions Cinema and Television as Entr'actes in History - Zielinski, Siegfried (Film Culture in Transition, 1999)
The production, distribution, and perception of moving images are undergoing a radical transformation. Ever-faster computers, digital technology, and microelectronic are joining forces to produce advanced audiovision -the media vanishing point of the 20th century. Very little will remain unchanged. The classic institutions for the mediation of film - cinema and television - are revealed to be no more than interludes in the broader history of the audiovisual media. This book interprets these changes not simply as a cultural loss but also as a challenge: the new audiovisions have to be confronted squarely to make strategic intervention possible. Audiovisions provides a historical underpinning for this active approach. Spanning 100 years, from the end of the 19th to the end of the 20th century, it reconstructs the complex genesis of cinema and television as historically relative - and thus finite - cultural forms, focussing on the dynamics and tension in the interaction between the apparatus and its uses. The book is also a plea for 'staying power' in studies of cultural technology and technological culture of film. Essayistic in style, it dispenses with complicated cross references and, instead, is structured around distinct historical phases. Montages of images and text provide supplemental information, contrast, and comment.